PEMANFAATAN TEKNOLOGI DIGITAL UNTUK MENINGKATKAN PENJUALAN KAMBING DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Ma’ruf, Mohammad Miftachu; Achmad Fahim; Moh Ya’kub (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2025)
The purpose of this study is to analyze how the use of digital technology can increase sales in the goat trading industry and how its implementation is viewed from the perspective of Islamic business ethics. Digital transformation has brought significant changes to trade patterns, including in traditional livestock sectors such as the goat trade. Through digital platforms such as social media, marketplaces, and instant messaging applications, goat breeders and traders can reach a wider market, increase price transparency, and expedite transaction processes. This research uses a qualitative case study approach to examine several goat trading businesses that have implemented digital technology in their operations. The research findings indicate that digital technology can significantly increase sales and business performance. From the perspective of Islamic business ethics, the use of this technology is considered positive if its application aligns with the principles of honesty (shidq), justice (adl), openness (transparency), and does not contain elements of fraud (gharar) or usury (riba). Thus, digitalization in the goat trade not only contributes to economic growth but can also align with Islamic values if managed ethically and responsibly